Cytotoxicity and Antiobesity Activity of Freeze-Dried Malus domestica, Canarium sp. and Averrhoa bilimbi Fruit - Sri Utami; Susi Endrini; Said Nafik; Seila Arumwardana; Rizal Rizal; Dwi Surya Artie; Dewani Tediana Yusepany; Hanna Sari Widya Kusuma; Wahyu Widowati (Majalah Obat Tradisional, 2021)
Obesity has a role in the development of diseases such as diabetes, cardiovascular disease and hyperlipidemia which is characterized by the increase of adipose tissue mass due to an imbalance of energy intake and expenditure. Freeze-dried fruits are well known to possess antiobesity activity. In this study, we have evaluated the antiobesity activity of freeze-dried fruit (M. domestica, Canarium sp., and A. bilimbi) using CHOL, G6PDH, TG level, and Oil Red O assay. The viability of 3T3-L1 cell in the Canarium sp. freeze-dried in the concentration of 12.50 µg/ml has a higher value compared to M. domestica and A. bilimbi. The measurements of CHOL, G6PDH, TG level, and Oil Red O assay of the M. domestica freeze-dried in the concentration of 75 μg/ml has higher inhibitory activity compared to the Canarium sp. and A. bilimbi freeze-dried. In the CHOL assay, M. domestica freeze-dried has a higher value compared to A. bilimbi and Canarium sp. In the G6PDH assay, the freeze-dried of M. domestica has the value of 49.56%, Canarium sp. (45.22%), and A. bilimbi (47.13%), while in the Oil Red O assay, M. domestica has inhibition activity of 62.63%, A. bilimbi 50.01% and Canarium sp. 44.13%. The level of TG showed that M. domestica has higher activity with the value of 60.61%, A. bilimbi 57.54%, while Canarium sp. 55.03%. The freeze-dried of M. domestica in the concentration of 75 μg/ml has good inhibitory activity of lipid compared to A. bilimbi and Canarium sp.